Effectiveness of Flipped Classroom Model Learning Using Microlearning on Buffer Solution Material - Puteri, Hana Alya; Paristiowati, Maria; Zulhipri, Zulhipri; Putri Hasibuan, Nur Azizah; Karyadi, Prita Atria (LAVOISIER: Chemistry Education Journal, 2024)
This study aims to determine the effectiveness of learning the flipped classroom model with microlearning on class XI buffer solution material. This research was conducted at SMA Negeri 99 Jakarta using a qualitative method. The sample used in this study was 35 students of class XI. This study refers to indicators of learning effectiveness, namely the management of learning implementation, communicative teaching-learning processes, student responses, learning activities, and learning outcomes. The instruments used in this study were observation, questionnaires, test questions, reflective journals, and interviews. The results of this study are that the flipped classroom learning model with microlearning is effective for use in buffer solution materials.